RETRACTED: A Blind Carrier Frequency Offset Estimation Scheme for OFDM Systems via Hybrid-ICA Algorithm - Amin Jalili; Mehdi Chehel Amirani; Saied Balaneshin Kordan (International Journal of Electrical and Computer Engineering (IJECE), 2014)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal). This article has been retracted by agreement between the author and the Editor-in-Chief. A request by the author to update the paper after publication resulted in an agreement to retract the paper by the Author and Editor-in-Chief. -------------------- This paper addresses a new iterative blind carrier frequency offset (CFO) estimator in orthogonal frequency-division multiplexing (OFDM) systems. In our scenario, relying on a hybrid independent component analysis (ICA) scheme, a blind frequency offset estimator is proposed for OFDM systems employing single antenna. The proposed estimator is a combination of the fast fixed-point ICA (FastICA) algorithm and the natural-gradient ICA algorithm, which inherits the fast convergence and high accuracy of theses algorithms, respectively. As a major advantage, the proposed estimator works in an efficient way in practical high-data-rate OFDM systems especially with large number of subcarriers. To demonstrate the efficiency of our proposed algorithm, numerical results are provided from computer simulations and comparisons are made with other existing CFO estimators in the literature. It is shown that by applying our proposed algorithm, the normalized mean-square error of the CFO estimator is decreased to a high extent. DOI:http://dx.doi.org/10.11591/ijece.v4i5.6533